The Assessment of Visuospatial Skills and Verbal Fluency in the Diagnosis of Alzheimer’s Disease - Berente, Dalida Borbala; Kamondi, Anita; Horvath, Andras Attila (Frontiers in Aging Neuroscience, 2022)
Background: In the diagnosis of Alzheimer’s disease (AD), examining memory is predominant. Our aim was to analyse the potential role of various cognitive domains in the cognitive evaluation of AD. Methods: 110 individuals with clinically defined AD and 45 healthy control participants underwent neuropsychological evaluation including Addenbrooke’s Cognitive Examination (ACE). AD patients were selected in three groups based on disease duration in years (y) (Group 1: ≤2y n=36; Group 2: 2-4y n=44, Group 3: ≥4y n=30). Covariance weighted intergroup comparison was performed on global cognitive score and subscores of cognitive domains. Spearman’s rho was applied to study the correlation between cognitive subscores and disease duration. Wilcoxon signed ranked test was used for within group analysis among ACE cognitive subscores. Results: Significant difference was found between ACE total scores among groups (χ2=119,1; p<0,001) with a high negative correlation (p<0,001; r: -0,643). With longer disease duration, all the subscores of ACE significantly decreased (p’s <0,001). Visuospatial score showed the strongest negative correlation with disease duration with a linear trajectory in decline (r: -0,85). In the early phase of cognitive decline, verbal fluency was the most impaired cognitive subdomain (normalized value: 0.64), and it was significantly reduced compared to all other subdomains (p’s<0.05). Conclusion: We found that impairment of verbal fluency is the most characteristic feature of early cognitive decline, therefore it might have crucial importance in the early detection of Alzheimer’s disease. Based on our results visuospatial assessment might be an ideal marker to monitor the progression of cognitive decline in AD. Key words: (3-5): Alzheimer’s disease, neuropsychology, cognitive domains, progression, diagnosis Introduction